Simple Resonant Power Converter Supplied by Photovoltaic for Ozonizer - Mochammad Facta; Hermawan .; Zainal Salam (IAES Indonesia Section, 2014)
Ozone gas (O3) is widely used in deodorization,decolourization, disinfection, bleaching processes, gas/airtreatment, chemical synthesis and recently in medicalapplications. Due the wide application of ozone then the ozonegenerator or ozonizer is urgently needed. A single switchresonant converter with ferrite transformer is proposed in thiswork. The prototype is constructed by two parts, first is ozonechamber and the second part is power converter with a singleswitch resonant converter and it supplied by photovoltaicsimulator. The converter is successful to convert 12 volt fromphotovoltaic to 1.89 kVpp high frequency voltage to ozonechamber. The ozone gas produce with the proposed system is 450ppm with oxygen as an input gas.